(untitled) (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2024)
This article is based on an overview of the challenges faced by HEIs in the branding process and then recommends appropriate strategies for university branding. The most important challenges facing HEIs are the inability to create a brand identity, difficulties in communicating the brand through appropriate branding activities, cultural issues affecting HEIs, pros and cons of alliances and partnerships, and inadequate infrastructural facilities.